Design and validation of a microfluidic device for blood–brain barrier monitoring and transport studies. (15th February 2018) - Ugolini, Giovanni Stefano; Occhetta, Paola; Saccani, Alessandra; Re, Francesca; Krol, Silke; Rasponi, Marco; Redaelli, Alberto
Abstract: In vitro blood–brain barrier models are highly relevant for drug screening and drug development studies, due to the challenging task of understanding the transport mechanism of drug molecules through the blood–brain barrier towards the brain tissue. In this respect, microfluidics holds potential for providing microsystems that require low amounts of cells and reagent and can be potentially multiplexed for increasing the ease and throughput of the drug screening process. We here describe the design, development and validation of a microfluidic device for endothelial blood–brain barrier cell transport studies. The device comprises of two microstructured layers (top culture chamber and bottom collection chamber) sandwiching a porous membrane for the cell culture. Microstructured layers include two pairs of physical electrodes, embedded into the device layers by geometrically defined guiding channels with computationally optimized positions. These electrodes allow the use of commercial electrical measurement systems for monitoring trans-endothelial electrical resistance (TEER). We employed the designed device for performing preliminary assessment of endothelial barrier formation with murine brain endothelial cells (Br-bEnd5). Results demonstrate that cellular junctional complexes effectively form in the cultures (expression of VE-Cadherin and ZO-1) and that the TEER monitoring systems effectively detects an increase of resistance of the cultured cell layers indicative of tight junction formation. Finally, we validate the use of the described microsystem for drug transport studies demonstrating that Br-bEnd5 cells significantly hinder the transport of molecules (40 kDa and 4 kDa dextran) from the top culture chamber to the bottom collection chamber.